2001
DOI: 10.1164/ajrccm.163.1.2005069
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor- β1 Induces Phenotypic Modulation of Human Lung Fibroblasts to Myofibroblast Through a c-Jun-NH2-Terminal Kinase-Dependent Pathway

Abstract: Myofibroblasts play an important role in the fibrogenic process of pulmonary fibrosis. Transforming growth factor (TGF)-beta is well known to induce the phenotypic modulation of fibroblasts to myofibroblasts; however, the intracellular signal regulating induction of the myofibroblastic phenotype of human lung fibroblasts (HLF) has not been determined. In the present study, we examined the role of the mitogen-activated protein kinase (MAPK) superfamily in inducing the phenotypic modulation of HLF to myofibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 23 publications
6
153
1
1
Order By: Relevance
“…A study using lung fibroblasts found that TGF-β1 up-regulated c-Jun NH 2 -terminal kinase (JNK), p38 MAPK, and extracellular regulated kinase (ERK) phosphorylation and activity. However, only CEP-1347 (a specific inhibitor of the JNK-mediated signaling pathway), but not SB 203580 or PD 98059 (inhibitors of p38 MAPK and ERK kinase respectively) decreased the TGF-β1-induced myofibroblast differentiation in a dose dependent manner [Hashimoto et al, 2001]. These data suggested that TGF-β1-activated JNK pathway regulated myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 90%
“…A study using lung fibroblasts found that TGF-β1 up-regulated c-Jun NH 2 -terminal kinase (JNK), p38 MAPK, and extracellular regulated kinase (ERK) phosphorylation and activity. However, only CEP-1347 (a specific inhibitor of the JNK-mediated signaling pathway), but not SB 203580 or PD 98059 (inhibitors of p38 MAPK and ERK kinase respectively) decreased the TGF-β1-induced myofibroblast differentiation in a dose dependent manner [Hashimoto et al, 2001]. These data suggested that TGF-β1-activated JNK pathway regulated myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 90%
“…Fibroblasts deficient in JNK make excess TGF␤ (Ventura et al, 2004), and overexpression of the JNK target c-jun blocks induction of a generic Smad3-dependent reporter (Verrecchia et al, 2001;Leask et al, 2003). Conversely, TGF␤ induces ␣-SMA in a JNK-dependent manner (Hashimoto et al, 2001) and c-jun augments TGF␤-induction of 12-O-tetradecanoyl-13-acetate (TPA)-responsive gene promoter (TRE) elements that contain AP-1 sites (Zhang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Smad7 prevents the phosphorylation of Smad2 or Smad3 and, consequently, nuclear translocation. CEP-1347, an inhibitor of JNK-mediated signalling and currently in clinical trial for Alzheimer's and Parkinson's disease, inhibits TGF-β-induced α-SMA expression in fibroblasts [235]. Halofuginone, an antifibrotic agent, h Human origin (unless mentioned otherwise); § fibroblasts were pretreated with TGF-β.…”
Section: The Stroma: a Target For Cancer Therapymentioning
confidence: 99%